Enhancing Students’ Technopreneurship Intention through Team-Based Project Learning: A CIPP Evaluation Approach - Ahmad Jaenudin; Aulia Prima Kharismaputra; Aan Ikhsananto; Dwi Puji Astuti (Journal of Economics Education and Entrepreneurship, 2026)
The development of the digital economy requires higher education institutions to produce graduates who possess not only technological literacy but also technology-based entrepreneurial orientation (technopreneurship). This study aimed to examine the effectiveness of the team-based project learning model through the Context, Input, Process, and Product (CIPP) evaluation approach. The study employed a quantitative approach using a true experimental design with a pretest-posttest control group design. The sample consisted of 100 students of the Economic Education Study Program at Universitas Negeri Semarang, divided into experimental and control groups with 50 students in each group. Data were collected using a technopreneurship intention questionnaire and a CIPP evaluation instrument that had met validity and reliability requirements. Data analysis was conducted using an independent sample t-test and Cohen’s d effect size with the assistance of IBM SPSS Statistics 26. The findings revealed no significant difference at the pretest stage (sig. = 0.367 > 0.05), but a significant difference was found at the posttest stage (sig. = 0.000 < 0.05), with the experimental group obtaining a higher mean score than the control group. The CIPP evaluation showed that the learning implementation was categorized as good with an average score of 83.2%, while the process component achieved the highest score of 85.6%. The effect size value of 1.01 indicated a strong effect on improving students’ technopreneurship intention. These findings confirm that the integration of team-based project learning and CIPP evaluation is effective in creating contextual, collaborative, and experiential entrepreneurship learning in higher education.